Gingivitis and Oral Health Diseases Related to Pregnancy - Talebessy, Rio; Steffi Cecilia (Crown: Journal of Dentistry and Health Research, 2023)
Pregnancy gingivitis is a common condition characterized by gum inflammation, swelling, and bleeding. Hormonal fluctuations during pregnancy can increase susceptibility to dental infections, particularly in teeth and gums. Factors such as hormonal fluctuations, morning sickness, dietary changes, heightened gum sensitivity, and decreased dental care practices can contribute to this issue. Although hormonal changes do not directly cause dental infections, they can heighten the susceptibility to gum issues and potentially exacerbate the progression of dental infections. This review provides a comprehensive description of pregnancy gingivitis and its contributing factors. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding gingivitis and hormonal changes in pregnancy. The search was performed using the terms: (1) "gingivitis" OR "gingivitis pregnancy" OR "gingival inflammation” AND (2) "pregnancy". Within the scope of the review, a total of three quantitative studies were incorporated. In summary, gingivitis during pregnancy is a condition characterized by hormonal fluctuations, particularly heightened levels of estrogen and progesterone. These fluctuations can affect gum health, leading to heightened blood circulation, sensitivity to plaque formation, and changes in gum size and shape.